Communication, Goals, and Counterexamples in Syllogistic Reasoning - Vargas, Francisco; Stenning, Keith (Frontiers in Education, 2020)
We report on a study on syllogistic reasoning conceived with the idea that subjects’ performance in experiments is highly dependent on the communicative situations in which the particular task is framed. From this perspective, we describe the results of Experiment 1 comparing the performance of undergraduate students in 5 different tasks. This between-subjects comparison inspires a within-subject intervention design (Experiment 2). The variations introduced on traditional experimental tasks and settings include two main dimensions. The first one focuses on reshaping the context (the pragmatics of the communication situations faced) along the dimension of cooperative vs. adversarial attitudes. The second one consists of rendering explicit the construction/representation of counterexamples, a crucial aspect in the definition of deduction (in the classical semantic sense). We obtain evidence on the possibility of a significant switch in students’ performance and the strategies they follow. Syllogistic reasoning is seen here as a controlled microcosm informative enough to provide insights and we suggest strategies for wider contexts of reasoning, argumentation and proof.